In vitro evaluation of fracture resistance of teeth restored with ceramic inlays by two undercut elimination techniques - Mirzayi M.; Ghavam M.; Emami Meibodi Z. (Tehran University of Medical Sciences, 2008)
"nBackground and Aim: Polymerization shrinkage of resin cements during setting leads to stress on teeth receiving indirect esthetic restorations. Some methods like blocking out undercuts during cavity preparation with glass Ionomer can reduce the mass of resin cement and therefore the amount of stress. The aim of this study was to evaluate the fracture resistance of molar teeth, receiving class I ceramic inlays with two different methods of blocking out undercut. "nMaterials and Methods: In this experimental study, thirty intact molar teeth were randomly divided into three groups of 10 each. One group was maintained intact as the control group. Similar class I cavities with identical undercuts were prepared on the other groups. In group 2 the undercut was filled with light cured glass Ionomer (vitremer 3M) before making impression, and in group 3 they were blocked out in the lab before preparation of the inlay. All the teeth in test groups were restored with indirect ceramic inlays.(vitadur - Alpha/ single bond / Rely X ARC). After thermocycling load causing fracture was assessed by universal testing machine. All the specimens were examined under a steriomicroscope (X40) to determine type of fracture. The results were analyzed by one way ANOVA and Tukey HSD tests. P< 0.05 was considered as the level of significance. "nResults: The restored groups showed significantly less fracture resistance than the control group. The difference between two test groups was not significant. The fracture in group2 had less destruction. "nConclusion: According to the findings of this study, blocking out the undercut with two different methods (using glass ionomer/ or blocking it out on the die) made no diferrence in fracture resistance.